2021
DOI: 10.1038/s41531-021-00163-0
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic morphology predicts the onset of freezing of gait in Parkinson’s disease

Abstract: The onset of freezing of gait (FOG) in Parkinson’s disease (PD) is a critical milestone, marked by a higher risk of falls and reduced quality of life. FOG is associated with alterations in subcortical neural circuits, yet no study has assessed whether subcortical morphology can predict the onset of clinical FOG. In this prospective multimodal neuroimaging cohort study, we performed vertex-based analysis of grey matter morphology in fifty-seven individuals with PD at study entry and two years later. We also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…The thalamus, as a key node in the basal ganglia-thalamocortical and cerebellothalamocortical circuits, plays a crucial role in the modulation of gait. Thalamic morphology predicts the onset of FOG in PD (5). Although isolated thalamus lesions seldom induce FOG, disruption of thalamic neural activity and functional connections contribute to the development of FOG.…”
Section: Introductionmentioning
confidence: 96%
“…The thalamus, as a key node in the basal ganglia-thalamocortical and cerebellothalamocortical circuits, plays a crucial role in the modulation of gait. Thalamic morphology predicts the onset of FOG in PD (5). Although isolated thalamus lesions seldom induce FOG, disruption of thalamic neural activity and functional connections contribute to the development of FOG.…”
Section: Introductionmentioning
confidence: 96%
“…This work adds to a growing body of knowledge demonstrating structural and functional changes in the thalamus – and in the connections of the thalamus to other brain regions – in PD patients with FOG. In a prospective MRI neuroimaging study, D’Cruz et al 58 showed local inflations in bilateral thalami in patients who presented with or would later develop FOG. These inflations involved medial thalamic sub-nuclei volumes which are highly innervated by NA pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This work adds to a growing body of knowledge demonstrating structural and functional changes in the thalamus -and in the connections of the thalamus to other brain regions -in PD patients with FOG. In a prospective MRI neuroimaging study, D'Cruz et al 58 Other studies have shown several anatomical changes in connections between the thalamus and other brain regions in FOG, including some known to be crucial for balance and gait. These include diminished structural connectivity between the thalamus and mesencephalic locomotor region and reduced thalamic fiber tracts in the right hemisphere in FOG 59 and more pronounced white matter abnormalities in multiple tracts connecting to the thalamus in FOG 60 .…”
Section: Structural and Functional Changes In The Thalamus In Fogmentioning
confidence: 99%
“…Connections of the medial thalamic nuclei with cortical associative and limbic areas are enhanced with the appearance of FOG in patients with PD 47 . The increased coupling to those nonmotor cortical areas has been interpreted as compensation to deficient sensorimotor integration or reinforcement of malfunctioning circuits 48 . The cerebellum, a major player in postural control, may also be involved in FOG mechanisms and FOG triggering.…”
Section: Discussion Of the Current Knowledge On Pathophysiologymentioning
confidence: 99%